2010
DOI: 10.1007/s00198-010-1315-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of fall-related fractures to social deprivation

Abstract: This is the first study to show the relationship between fall-related fractures and social deprivation in older patients. We believe that the decreased incidence of proximal femoral fractures, and the lower average age of patients with fall-related fractures, in the socially deprived relates to the relative life expectancies in the different deprivation deciles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…In a recent study, Court-Brown et al [7] demonstrated the influence of social deprivation on the incidence of fractures from simple falls, and our results confirm that this influence also extends to fractures related to falls on stairs. Notably the greatest difference between patient groups was seen between Quintiles 4 and 5, with far less variation identified between the Quintiles 1, 2, and 3.…”
Section: Isrn Epidemiologysupporting
confidence: 86%
See 2 more Smart Citations
“…In a recent study, Court-Brown et al [7] demonstrated the influence of social deprivation on the incidence of fractures from simple falls, and our results confirm that this influence also extends to fractures related to falls on stairs. Notably the greatest difference between patient groups was seen between Quintiles 4 and 5, with far less variation identified between the Quintiles 1, 2, and 3.…”
Section: Isrn Epidemiologysupporting
confidence: 86%
“…The Carstairs score is a -score based on overcrowding, male unemployment, social class, and car ownership. It has been extensively used to examine social deprivation in orthopaedic surgery [7,8,12] and other branches of medicine [9,13]. The Carstairs score can be used to divide the population of Scotland into five equal quintiles, with Quintile 1 (Q1) being the most affluent and Quintile 5 (Q5) being the most deprived.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the reverse relationship has been reported in Spain where hip fracture risk was higher in the least deprived compared to most deprived areas, possibly explained by the protective effects of obesity for the hip (12). In the UK, a number of studies have identified an association between worsening deprivation and higher hip fracture incidence (13)(14)(15)(16); but this has not been consistently demonstrated albeit by studies of varying lengths (17,18). In addition, recent evidence suggests the relationship between deprivation and hip fracture risk may be stronger in men than women (16), potentially explained by differing predispositions in men and women towards lifestyle habits that increase fracture risk, such as tobacco and heavy alcohol consumption (19,20).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have also identified the occurrence of ‘post-fall syndrome’ in fallers. Individuals who have a fear of falling appear to enter a debilitating spiral of loss of confidence, functional decline and social deprivation, physical frailty, falls, and loss of independence [11,12]. Hypothermia, pressure-related injuries and infections may also result from falls [13].…”
Section: Introductionmentioning
confidence: 99%